Preoperative predictors of recurrence beyond Milan criteria in hepatocellular carcinoma patients treated with frontline liver resection. (March 2023) - Pelizzaro, F.; Trevisani, F.; Vitale, A.; Cillo, U.; Piscaglia, F.; Missale, G.; Sangiovanni, A.; Foschi, F.G.; Cabibbo, G.; Caturelli, E.; Di Marco, M.; Azzaroli, F.; et al.
Abstract : Introduction: Hepatocellular carcinoma (HCC) recurrence is common in patients treated with liver resection (LR). Salvage liver transplantation (LT) may be an option provided that a transplantable recurrence has occurred. Aim: We aimed to assess incidence and preoperative predictors of recurrence beyond Milan criteria (MC) in patients with small (≤ 5 cm) single HCC treated with first-line LR. Materials and Methods: Data of 512 patients with single HCC ≤5 cm treated with frontline LR were retrieved from the Italian Liver Cancer (ITA.LI.CA) database. Incidence and predictors of recurrence beyond MC was compared across two groups according to tumor diameter (HCC ≤3 cm vs. >3 cm). Results: During a median follow-up of 4.2 years, the overall recurrence rate was 55.9%. Only 18.0% of patients had a first recurrence beyond MC (14.0% in the ≤3 cm group and 23.9% in the >3 group; p=0.005), while the overall recurrence rate beyond MC was 30.3% (25.1% and 38.0% patients in the ≤3 cm and >3 cm groups, respectively; p=0.002) (Figure). Compared to those with larger tumors, patients with HCC ≤3 cm had a longer recurrence-free survival (4.0 [95% CI 3.3-4.7] vs. 2.5 [95% CI 2.0-3.0] years; p=0.002) and overall survival (9.9 [95% CI 6.5-13.4] vs. 7.8 [95% CI 5.7-9.9] years; p=0.008). HCC size and alpha-fetoprotein (AFP) level at the time of LR were independent predictors of recurrence beyond MC. A subanalysis in patients with "ab initio" potentially transplantable HCC confirmed these results. Conclusions: Despite the high recurrence rate, LR for single HCC ≤ 5 cm offers excellent long-term survival. Recurrence beyond MC is predicted by HCC size and AFP levels. Referral for salvage LT should be immediate at the first HCC recurrence, but high-risk patients (HCC >3 cm and high AFP) could be considered for frontline LT or listed for transplantation even before recurrence.